Prevalence and predictors of HIV-related disability among people living with HIV in Nigeria - Temitope S. Oladejo; Hellen Myezwa; Adedayo T. Ajidahun; Sam Ibeneme (AOSIS, 2024)
Background: People living with human immunodeficiency virus (PLWH) live longer, but experience human immunodeficiency virus (HIV)-related comorbidities and disabilities that lower their quality of life. Understanding the prevalence, risk factors, and disability patterns is crucial for tailored interventions. Objectives: To explore the prevalence and predictors of HIV-related disability among PLWH in Nigeria. Method: This cross-sectional survey involved 385 PLWH, exploring demographic data, HIV history, recent symptoms, disability (measured by the WHO Disability Assessment Schedule-WHODAS 2.0). Descriptive statistics summarised the data, all variables were entered into univariate and multivariate regression models. IBM SPSS 25® was used for all analyses at a 95% confidence level. Results: The prevalence of disability among PLWH was 39.5%, the mean age was 42.2 ± 10.43 years, and 73% of the participants were females. Factors significantly associated with disability were marital status (p = 0.009) and level of education (p = 0.001). Conclusion: The study reveals a prevalence of disability (39.5%) among PLWH on antiretroviral therapy (ART), emphasising the need for tailored interventions considering socio-demographic factors. Continuous screening, risk identification, and effective management strategies are imperative, recognising disability as an indicator of health and quality of life. Clinical implications: With PLWH experiencing increased life expectancy, the study underscores the need for an informed patient-centred approach to care, recognising the specific challenges faced by PLWH in Nigeria and guiding the development of targeted interventions to enhance both functional outcomes and overall well-being.